Prevalence and Consequences of Injuries in Powerlifting: A Cross-sectional Study. Issue 5 (14th May 2018) - Strömbäck, Edit; Aasa, Ulrika; Gilenstam, Kajsa; Berglund, Lars
Background: Powerlifting consists of the squat, bench press, and dead lift, and extreme loads are lifted during training and competitions. Previous studies, which have defined an injury as an event that causes an interruption in training or competitions, have reported a relatively low frequency of powerlifting injuries (1.0-4.4 injuries/1000 hours of training). No previous study has investigated the prevalence of injuries, defined as a condition of pain or impairment of bodily function that affects powerlifters' training, in a balanced sample of men and women, and no studies have established possible risk factors for an injury. Purpose: To investigate the prevalence, localization, and characterization of injuries among Swedish subelite classic powerlifters, with an emphasis on differences between men and women, and to investigate whether training and lifestyle factors are associated with an injury. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 53 female and 51 male Swedish subelite powerlifters answered an online questionnaire including questions about background characteristics, training habits, and lifestyle factors. The main part of the questionnaire included questions about injuries and their consequences. An injury was defined as a condition of pain or impairment of bodily function that affects powerlifters' training. Results: Seventy percent (73/104) of participants were currently injured, and 87% (83/95) had experienced an injury within the past 12 months. The lumbopelvic region, shoulder, and hip were the most commonly injured areas for both sexes. Women experienced a significantly greater frequency of injuries in the neck and thoracic region than men. Injuries seemed to occur during training, although only 16% (11/70) of those currently injured had to completely refrain from training. Training frequency, greater personal best in the dead lift, injury onset during bench-press and dead-lift training, use of straps, alcohol consumption, and dietary issues were associated with current injuries. Conclusion: Injuries are very common in subelite powerlifters. Men and women report similar injury frequencies but different anatomic locations. These injuries do not prevent powerlifters from training and competing, but they may change the content of training sessions. Why powerlifters develop injuries is still unclear; however, it is likely that the management of training loads and optimization of the lifting technique during the squat, bench press, and dead lift are of importance.